A novel phase noise measurement of phase modulation microwave photonic links. Issue 13 (19th July 2016) - Ye, Quanyi; Gao, Yingjie; Yang, Chun
Abstract: Microwave photonic links can provide many advantages over traditional coaxial due to its low loss, small size, lightweight, large bandwidth and immunity to external interference. In this paper, a novel phase noise measurement system is built, since the input signal and the power supply noise can be effectively cancelled by a two-arm configuration without the phase locking. Using this approach, the phase noise performance of the 10-GHz phase modulation photonic link has been measured for the first time, evaluated the values of −124 dBc/Hz at 1 kHz offset and −132 dBc/Hz at 10 kHz offset is obtained. Theoretical analysis on the phase noise measurement system calibration is also discussed.